Generation of sclerosant foams by mechanical methods increases the foam temperature. (August 2017) - Tan, Lulu; Wong, Kaichung; Connor, David; Fakhim, Babak; Behnia, Masud; Parsi, Kurosh
Objective: To investigate the effect of agitation on foam temperature. Methods: Sodium tetradecyl sulphate and polidocanol were used. Prior to foam generation, the sclerosant and all constituent equipment were cooled to 4–25℃ and compared with cooling the sclerosant only. Foam was generated using a modified Tessari method. During foam agitation, the temperature change was measured using a thermocouple for 120 s. Results: Pre-cooling all the constituent equipment resulted in a cooler foam in comparison with only cooling the sclerosant. A starting temperature of 4℃ produced average foam temperatures of 12.5 and 13.2℃ for sodium tetradecyl sulphate and polidocanol, respectively. It was also found that only cooling the liquid sclerosant provided minimal cooling to the final foam temperature, with the temperature 20 and 20.5℃ for sodium tetradecyl sulphate and polidocanol, respectively. Conclusion: The foam generation process has a noticeable impact on final foam temperature and needs to be taken into consideration when creating foam.